1998
DOI: 10.1165/ajrcmb.18.1.2813
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Release of Interleukin-8 by Human Airway Smooth Muscle Cells: Inhibition by Th-2 Cytokines and Corticosteroids

Abstract: Interleukin (IL)-8 is a C-X-C chemokine that potently chemoattracts and activates neutrophils. We determined whether IL-8 could be produced by human airway smooth muscle cells in culture and examined its regulation. TNF-alpha stimulated IL-8 mRNA expression and protein release in a time- and dose-dependent manner, whereas IFN-gamma alone had no effect. Both cytokines together did not induce greater IL-8 release compared to TNF-alpha alone. IL-1beta was more potent in inducing IL-8 release and, together with TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 28 publications
(20 reference statements)
9
106
0
2
Order By: Relevance
“…IL-8, RAN-TES, and eotaxin production by human ASMC is induced by TNF-␣ but not IFN-␥. Furthermore, although IFN-␥ potentiates TNF-␣-induced RANTES release, it has no synergistic effects on TNF-␣-induced IL-8 or eotaxin release (11,35,36,51). Thus the relative presence or absence of IFN-␥ and TNF-␣ in the inflammatory milieu may direct the pattern of ASMC chemokine synthesis and hence the type of inflammatory cells recruited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-8, RAN-TES, and eotaxin production by human ASMC is induced by TNF-␣ but not IFN-␥. Furthermore, although IFN-␥ potentiates TNF-␣-induced RANTES release, it has no synergistic effects on TNF-␣-induced IL-8 or eotaxin release (11,35,36,51). Thus the relative presence or absence of IFN-␥ and TNF-␣ in the inflammatory milieu may direct the pattern of ASMC chemokine synthesis and hence the type of inflammatory cells recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are the most effective anti-inflammatory drugs for the treatment of asthma, and previous studies have demonstrated inhibitory effects of corticosteroids on ASMC cytokine and chemokine synthesis (35,36). Paradoxically, we observed marked upregulation of cytokine-stimulated FKN mRNA expression and protein synthesis in the presence of the corticosteroid dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence for the release of macrophage inflammatory protein-1a [30]. Following stimulation with IL-1b and bradykinin, airway smooth muscle cells can express and release IL-8, a potent neutrophil chemoattractant [35,36].…”
Section: Chemokinesmentioning
confidence: 99%
“…H uman airway smooth muscle cells (ASMC), 3 apart from having contractile and proliferative functions, may contribute directly to airway inflammation through their synthesis of proinflammatory cytokines and chemokines (1). ASMC in culture can be stimulated to produce a wide array of cytokines and chemokines, such as GM-CSF, RANTES, eotaxin, IL-6, IL-8, and growth-related oncogene protein-␣ (GRO-␣) in response to inflammatory mediators (2-7), and may therefore be important effector cells in lung inflammation.…”
mentioning
confidence: 99%